RELASI PENGETAHUAN DAN KEKUASAAN DALAM FORMASI DISKURSIF BIO-POLITIK MICHEL FOUCAULT - Wa Ode Nurul Yani (Dialektika, 2016)
Gaze in conceptualizing Foucault illustrated as "a language without words" characterized by the power of doctors in diagnosis verdicts and statements about its knowledge. Gaze in power marked by authoritarianism doctor doctor in a dialogue with the patient and statements about the verdict of the disease (diagnosis) is strengthened by medical technology. Capitalist medical building health clinics, health centers and hospitals to accommodate the power of education for physicians. People have become very dependent on the physician in determining a person is sick or healthy at the same time to seek a remedy for the illness. People are willing to pay dearly to get healing. This reality puts the medical profession has an important value in the society. The position of the doctor very political trying to retain power. Doctors prefer to give medicine instead of communicating with the public about healthy living. Doctors on behalf of their knowledge, acting authority in judging a person is sick or recovering. If the doctor-centrism is not supported by the governance of public health was good, then heal the sick by bringing to the doctors just throw public money alone, without the support of good governance in the field of public health.